External load transition practices from pre-season to in-season. A case study in elite female professional soccer players - Oliveira, R.; Morgans, R.; Fernandes, R.; Brito, J. P.; Espada, M. C.; Santos, F. J. (PLOS ONE, 2024)
The study aim was to compare the external load during varying microcycles (M1-M4 during pre-season and M5 during the in-season) in elite female Portuguese soccer players and to describe external load variations between differing Ms. Fourteen first-team players participated in the study (age 23.29 ± 3.19 years, weight 59.14 ± 6.87 kg, height 1.66 ± 0.08 m). Load measures included total distance, high-speed running (HSR) distance (=15 km/h), number of accelerations and decelerations [acceleration 1 (ACC1), >1-2 m/s; acceleration 2 (ACC2), >2-3 m/s; acceleration 3 (ACC3), >3-4 m/s; acceleration 4 (ACC4), >4 m/s] and decelerations [deceleration 1 (DEC1), <1-2 m/s; deceleration 2 (DEC2), <2-3 m/s; deceleration 3 (DEC3), <3-4 m/s; deceleration 4 (DEC4), <4 m/s]. M1 showed higher values of total distance, ACC1, ACC2, ACC3, DEC2, DEC3 and DEC4 than M2 (p = <0.001-0.04), although HSR was higher in M2 (p < 0.001). M2 showed lower values of HSR, ACC1, DEC1, DEC2, DEC3 than M3 (p = 0.001-0.04). M3 reported higher values of total distance, ACC1, ACC2, DEC1, DEC2 than M4 (p = <0.001-0.03), while M4 only found higher values of ACC4 and DEC4 than M5 (both, p = 0.01). The highest values occurred in M3 for the majority of external load metrics (except ACC3, ACC4, and DEC4 which were higher in M4). However, during the transition from M4 to M5, only ACC4 and DEC4 decreased with all other measures maintained, thus supporting the notion to maintain similar loading patterns during official competition.